Role of forkhead box protein 2 (FOXP2) in oral-motor abilities of preterm infants: A brief literature review - Mauliza , Mauliza; Dimiati, Herlina; Akmal, Muslim; Imran, Imran (Narra Sains Indonesia, 2023)
Preterm infants, born before the 37-week gestation period, have limited storage for nutrients at birth and are vulnerable to poor feeding, severe nutritional deficits and growth retardation. The immature gastrointestinal system leads preterm infants to experience a delay in initiating enteral nutrition. Inappropriate feeding can cause acute and long-term morbidity, prolonged hospitalization and increased treatment cost. Generally, preterm infants that are born after 32 weeks of gestation without severe comorbidities do not have dysphagia and should start oral feeding soon after birth. Preterm infants should have well-developed sucking-swallowing-breathing coordination by 32–34 weeks of gestational age. However, some infants take days or weeks to master the skill. The oral feeding development involves forkhead box protein 2 (FOXP2)-expressing neurons that are found in the deep layers of the cortex, basal ganglia, parts of the thalamus and Purkinje cells of the cerebellum. In mammals, these areas belong to the brain network circuits working for motor coordination in learning and acquiring sensorimotor skills. This review aimed to describe the role of FOXP2 in oral-motor skills in preterm infants, including oral feeding, sucking-swallowing-breathing coordination and language development. The oral-motor skills development could be an early predictor for language delay in premature infants, representing a vulnerable group susceptible to such delays.